Genetic testing for familial hypercholesterolemia in a Finnish cohort of patients with premature coronary artery disease and elevated LDL-C levels - Jokiniitty, Antti; Eskola, Markku; Metso, Saara; Bogsrud, Martin; Huhtala, Heini; Saarela, Tanja (Frontiers in Cardiovascular Medicine, 2024)
Background Based on Finnish LDLR-founder variations, the prevalence of familial hypercholesterolemia (FH) in Finland is estimated to be at least 1:600. Patients with FH have increased risk of premature coronary artery disease (CAD) and thus the prevalence of FH is expected to be higher in this subgroup. Objective To assess the prevalence of monogenic FH in a Finnish cohort of patients with premature CAD and elevated low-density lipoprotein cholesterol (LDL-C) levels. Methods Among 28,295 patients undergoing angiography at Heart Hospital at Tampere University Hospital between 2007 and 2017, we identified 162 patients diagnosed with premature CAD (men aged <55 years and women aged <60 years) and history of high LDL-C (≥5 mmol/L) levels without secondary causes of hypercholesterolemia. Clinical probability of FH was estimated, and genetic testing of FH was carried out in 80 patients with informed consent. Results Of the 80 patients with premature CAD and history of high LDL-C levels, 70% were men; the age at diagnosis of CAD for male and female patients was 48 and 53 years, respectively. In total, 58 (73%) patients had probable (n = 54) or definite (n = 4) FH based on Dutch Lipid Clinic Network criteria. A pathogenic variant of FH was found in five (6%) patients. Prevalence of the genetically verified FH was 1:16. The FH variant was found in 75% of patients with definite FH. Conclusions The prevalence of genetically verified FH was 1:16 among patients with premature CAD and elevated LDL-C level, which is 38 times higher than the estimated prevalence of 1:600 in the general Finnish population.